Cost of operating room time for endovascular transcatheter aortic valve replacement. (3rd October 2019) - Potter, Brian J.; Ann Thompson, Christin
Abstract: Background: Procedural efficiencies can contribute to cost reductions in transcatheter aortic valve replacement procedures (TAVR). The objective of this study is to determine operating room (OR) variable cost per minute in endovascular TAVR procedures, in a real-world hospital setting. Methods: Using Premier data from January 2015–June 2016 for patients undergoing a primary endovascular TAVR (primary ICD-9 code of 35.05, ICD-10 code of 02RF37Z, 02RF38Z, 02RF3JZ, or 02RF3KZ) procedure, the OR cost per minute was calculated for each patient by dividing the total hospital OR variable cost by the OR time (minutes). Results: Of the 4, 573 patients in the cohort, the average age was 80 years, 77% were admitted electively, and the vast majority were discharged home with (30%) or without (45%) home care. Median OR time for endovascular TAVR procedures was 180 min. The trimmed mean OR cost per minute was 43.59 (SD = 28.68). When stratified by Elixhauser Risk score and Charlson comorbidity index, OR cost per minute increased with higher risk and comorbidity ( p < 0.0001 and p < 0.041, respectively). Conclusions: This contemporary estimate of the real-world variable OR cost per minute provides researchers with a critical parameter to refine economic models of TAVR and aid clinical program directors in resource planning according to a priori risk and comorbidity.